The Late Pleistocene-Holocene sedimentary evolution of the Sines Contourite Drift (SW Portuguese Margin): A multiproxy approach - Manuel António Teixeira; Pedro Terrinha; C Roque; Antje H L Voelker; Pedro F Silva; Emilia Salgueiro; Fatima F Abrantes; Filipa Naughton; Anxo Mena; Gemma Ercilla; David Casas (PANGAEA, 2020)
The Sines Contourite Drift (SCD), located in the Alentejo margin, southwest Iberian continental margin, has been through many depositional phases in result of climatic variations and bottom current oscillations, which determined a variable depositional pattern and an irregular sedimentary evolution since the Late Pleistocene. The SCD, being in the main path of the Mediterranean Outflow Water (MOW), which greatly constrains the sedimentary building of this drift, constitutes the distal part of the Gulf of Cadiz Contourite Depositional System and its sedimentary evolution therefore reflects the history of MOW variations. In order to investigate this, we report on a multiproxy analysis of grain-size, carbon content and physical, geochemical, and environmental-magnetic properties on the AMS 14C dated 350-cm long gravity core CO14-GC-07, retrieved in the SCD, at 1425 meters water depth (mwd). The main objective is to reconstruct the evolution of the sedimentary package of the SCD from > 43 cal kyr BP to Present and bring new insights about the impact of bottom currents extquotesingle activity on the morphosedimentary evolution of the margin. Results show the existence of four distinct depositional phases in response to climate variations and bottom current oscillations during the Late Pleistocene-Holocene. Phase 1 (350-322 cm: >42.9 cal kyr BP) occurred in Marine Isotope Stage (MIS) 3 and presents silty-muddy sediments with presence of shell fragments and moderate bioturbation. Phase 2 (322-176 cm: >42.9 - ~30.5 cal kyr BP), which lasted from middle MIS 3 to the onset of MIS 2, reveals sediment coarsening towards the top limit, suggesting climate cooling and strong bottom current winnowing. Phase 3 (176-144 cm: ~30.5 - 17.1 cal kyr BP) covers most of MIS 2 prior to the last deglaciation and shows the sharpest variations on all sediment properties and the coarsest sediment facies, with Fe-rich layers associated with the increase of terrigenous input and sea-level regression that coincide with the enhancement of MOW. Phase 4 (144-0 cm: <17.1 cal kyr BP) is associated with the deglacial sea-level rise and represents a calmer depositional environment with finer sediments and increasing contributions of biogenic material. The MOW is the most prominent bottom current and the most active seabed shaping agent in the study area, whose vertical shifting during glacial (~800-2200 mwd) and interglacial (600-1500 mwd) periods is coincident with the most active morphosedimentary sector of the area, contributing to the development of landslide scars and sediment waves.